A-REVIEW OF PHYTOCHEMICAL, MEDICINAL AND NUTRITIONAL SIGNIFICANCE OF COLEUS AMBOINICUS WITH REFERENCE OF AYURVEDA (International Journal of Food and Nutritional Sciences, 2022)
Coleus amboinicus is one of the important aromatic plant amongst the Coleus family (Lamiaceae), which is grown as a garden-plant in India. A review of the records in both folkloric and scientific literatures indicates that Coleus amboinicus has been used in variety of diseases in traditional system of medicine in India and the use of the leaf juice as an antiepileptic, cough, fiver and other communicable diseases. In the present study an attempt has been made to validate information of Coleus extracts of leaf, stem and root extracts separately pointed to various health issues. On morpho-anatomical observation, the leaf and stem showed presence of numerous multicellular covering and glandular trichomes, whereas thin-walled phellogen is the distinct character of root. On physicochemical aspects, leaf shows higher extractive values, ash value, and moisture content compared to stem and root parts. All the three extracts on phytochemical screening showed the presence of alkaloids, flavonoids, saponins, tannins, triterpenoids, and only leaf and stem extracts have shown the presence of carotenoids in addition. The anticonvulsant potency was found to be more with leaf extract than stem extract and least in root extract. Total phenolics, flavonoids, alkaloids and saponin contents were also found to be more in the leaf extract compared to stem extract and least in root extract. Results from these studies provide a significant rationale for the traditional use of this plant as an anticonvulsant. The leaf extract shown to be more prominent in all the aspects.